CHATBOT TUMBUH KEMBANG ANAK MENGGUNAKAN GOOGLE DIALOGFLOW UNTUK POSYANDU MAWAR SUKORAME KEDIRI - Muhammad Hamdan Fairuz Zabadi; Selvia Ferdiana Kusuma, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The Golden Age Period (0-5 years) is a critical phase in a child's growth and development, requiring special attention to prevent issues such as stunting, underweight, and wasting, which remain prevalent in Indonesia. Posyandu Mawar Sukorame in Kediri plays a role in monitoring child development, but foster mothers often struggle to obtain accurate counseling and information. This project developed a Google DialogFlow-based chatbot to provide interactive information and counseling related to child growth and development, aiming to improve foster mothers' access to quality services. The methods used include needs analysis, design, development, and testing of the chatbot. A qualitative descriptive approach was employed to understand the phenomena experienced by the research subjects. The results show that this chatbot is effective in enhancing foster mothers' understanding of child nutrition and development, as well as supporting the role of Posyandu in improving the quality of child health services.